2019
DOI: 10.3390/ijerph16071148
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition, Physical Fitness, Physical Activity and Nutrition in Polish and Spanish Male Students of Sports Sciences: Differences and Correlations

Abstract: It is important to study differences in body composition, physical fitness and lifestyle behaviours between university students from different countries to develop country-specific recommendations on health promotion to provide to students when transitioning to university. The present study aimed to analyse differences in body composition, physical fitness and lifestyle behaviours between Polish and Spanish students of Sports Sciences. One-hundred-and-eighty-six male students participated (81 from Poland and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
27
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 18 publications
8
27
0
3
Order By: Relevance
“…The discussed research among Polish and Spanish physical education students also showed statistically significant differences in the quality of food choices depending on country of origin, with an indication of a higher rate of both favorable and unfavorable food choices among Polish students. In other studies among Polish (from Gdańsk) and Spanish (from Murcia) physical education students, it was also confirmed that there is diversity in eating behaviors depending on country, with students from Murcia more often consuming seafood and dairy products, while students from Gdańsk consumed more vegetables [ 21 ]. Diversification of eating behavior depending on the geographical factor was also shown in research conducted among physical education students from Spain and Romania.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The discussed research among Polish and Spanish physical education students also showed statistically significant differences in the quality of food choices depending on country of origin, with an indication of a higher rate of both favorable and unfavorable food choices among Polish students. In other studies among Polish (from Gdańsk) and Spanish (from Murcia) physical education students, it was also confirmed that there is diversity in eating behaviors depending on country, with students from Murcia more often consuming seafood and dairy products, while students from Gdańsk consumed more vegetables [ 21 ]. Diversification of eating behavior depending on the geographical factor was also shown in research conducted among physical education students from Spain and Romania.…”
Section: Discussionmentioning
confidence: 65%
“…In the literature, works have been presented on the determinants of physical activity, which, however, did not allow clear identification of the moderators of the relationship between personality and physical activity [ 23 ]. In other studies on the health behaviors of physical education students from Gdańsk and Murcia, it was confirmed that there is diversity in certain aspects of lifestyle, with Spanish students showing more rational dietary choices [ 21 ]; this is not unequivocally confirmed in the authors’ research. The authors of research on the relationship between satisfaction with body mass, rational nutrition, health awareness and physical activity of students from various cultures (Egypt, Palestine, and Finland) [ 36 ] also suggested the justification for continuing research in various countries.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Regardless of the students' country of origin, it has been suggested to rationalise student lifestyle in a way that promotes early prevention of chronic diseases, such as obesity and diabetes (Lopez-Sanchez et al, 2019). These lifestyle differences can originate in different cultures, traditions and climatic factors (Northern vs. Southern Europe), and also from the implementation of effective health policies (Lopez-Sanchez et al, 2019). The cited authors also indicate the need for repeating research in various regions of Poland and Spain, something which was attempted in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this period of life, dietary habits and health attitudes which make it possible to function in adult life are shaped [1]. Physical fitness of individuals from this age group has nearly all features of motor abilities of an adult and at the same time, the performed movements adapt to activities connected with future work and participation in various forms of physical recreation [2,3].…”
Section: Introductionmentioning
confidence: 99%